Mechanical and Electronic Properties of Fe(II) Doped Calcite: Ab Initio Calculations - Zhangci Wu; Xiao Zhi; Fujie Jia; Jiayuan Ye; Neng Li (Crystals, 2025)
Calcite (CaCO3), a widely used mineral in materials science and environmental engineering, exhibits excellent stability but has limited mechanical strength and a wide electronic band gap, restricting its broader functional applications. To address these limitations, we systematically investigated the effects of Fe(II) doping on the electronic and mechanical properties of calcite using density functional theory calculations. The results reveal that Fe atoms preferentially form a layered distribution within the lattice and significantly alter the electronic structure, notably reducing the band gap through the introduction of Fe 3d-derived states near the Fermi level. Concurrently, the incorporation of Fe strengthens the elastic constants and enhances the shear resistance, especially in directions aligned with the dopant layering. These improvements are attributed to the strong Fe-O bonding and localized lattice distortions. Furthermore, the interplay between the dopant distribution and magnetic ordering suggests that spin polarization could serve as a potential handle for property tuning. This study highlights Fe-doped calcite as a promising candidate for functional mineral-based materials and provides theoretical insights into the magnetic and structural design of carbonate systems.